Employee Performance as a Driver of Economic Efficiency: The Role of Work Environment and Internal Communication through Job Satisfaction (Case Study at PT PLN ULP Singaraja) - Yudanta, Ida Bagus Komang Darma; Komang Krisna Heryanda,; Ni Luh Wayan Sayang Telagawathi, (International Journal of Economics Development Research (IJEDR), 2025)
The advancement of digital technology has significantly transformed workplace dynamics, particularly within public institutions such as BAPPEDA Bengkalis and PT PLN ULP Singaraja. This study investigates the influence of digital workload, employee loyalty, and individual innovation on employee performance, moderated by digital adaptation and analyzed across generational cohorts. Simultaneously, a quantitative explanatory study was conducted at PT PLN ULP Singaraja to examine how work environment, internal communication, and job satisfaction affect employee performance. Data were collected from 125 employees using a saturated sampling method, with statistical analysis conducted through multiple linear regression. Results show that work environment, internal communication, and job satisfaction each have a significant positive effect on performance both individually and simultaneously. Practical implications suggest enhancing workplace facilities, strengthening internal communication, and increasing job satisfaction through career development and welfare programs. Future research should broaden the scope to other organizational units and include additional internal and external factors such as digital competence, intrinsic motivation, and leadership style to gain deeper insights into performance determinants.